Land Trusts as Conservation Boundary Organizations in Rapidly Exurbanizing Landscapes: A Case Study from Southern Appalachia. Issue 10 (2nd October 2020) - Brownson, Katherine; Chappell, Jessica; Meador, Jason; Bloodgood, Jennifer; Howard, Jillian; Kosen, Linda; Burnett, Hannah; Gancos-Crawford, Tara; Guinessey, Elizabeth; Heynen, Nik; Mertzlufft, Caitlin; Ortiz, Sebastian; et al.
Abstract: Exurban development is occurring in many formerly rural areas nationwide, often outpacing the ability of institutions to update land use regulations. These pressures can negatively impact local ecosystems and natural resources, including reduced biodiversity and degraded water quality. Local nongovernmental organizations play an important role in promoting conservation in exurban landscapes, where there is relatively little regulatory and institutional infrastructure. Here, we draw on boundary organization theory to discuss how land trusts can function as boundary organizations, by using boundary objects and working as a bridge between community members, scientists, and governments to navigate complex conservation challenges. Mainspring Conservation Trust in southern Appalachia serves as a case study to explore methods for engaging and connecting diverse stakeholders. We show that land trusts can provide a flexible and necessary alternative to regulations for meeting conservation objectives by working at the boundary between science and local action.